Kompetisi Guru Pendidikan Agama Islam pada Madrasah Tsanawiyah di Kota Mataram - Yustiani S (Analisa: Journal of Social Science and Religion, 2014)
AbstractThis study aims to measure the difference in competence between certified teachers  and non certified teachers in Mataram. Teachers examined in this study are teachers of religion in MTs. This articleis a quantitative research using causal comperative method. The research design use factoral design 2x2. The technical of analysis data in this research include descriptive analysis, requirements test analysis, and inferential analysis. The study shows that here are differences in Islamic Education Teachers’ competence in MTs in Mataram. Further test shows that the results of certified teachers competency arebetter than the teachers who have not been certified. There is no difference in Islamic Education Teachers’ competence based on the teacher’s tenure. There is no interaction between teacher’s status and teacher’s tenure. This means that the status and tenure arethe two factors which are mutually independent. There were no differences between the student learning result who is taught by certified teachers and uncertified teachers in Mataram. There is difference in student learning result based on the teacher’s tenure.There is no interaction between student learning result based on the status and the tenure of teachers in Mataram. It is concluded that certified teachers in Mataram has a good profile.Keywords: Competence, Islamic Education Teachers, Certification. AbstrakPenelitian ini bertujuan untuk mengukur perbedaan kompetensi guru PAI MTs antara yang telah tersertifikasi maupun yang belum tersertifikasi di Kota Mataram. Pendekatan yang digunakan dalam penelitian ini adalah kuantitatif dengan metode perbandingan kausal (causal comparative) desain faktoral 2x2. Teknis analisis data dalam penelitian ini meliputi analisis deskripstif, uji persyaratan, dan analisis inferensial. Hasil penelitian ini diperoleh 7 temuan sebagai berikut. (1) Terdapat perbedaan kompetensi guru PAI MTs di kota Mataram. Hasil uji lanjut diketahui bahwa kompetensi guru yang tersertifikasi lebihbaik daripada guru yang belum tersertifikasi. (2) Tidak terdapat perbedaan kompetensi guru PAI MTs Kota Mataram dilihat dari masa kerja guru.(3) Tidak ada interaksi antara status guru dengan masa kerja guru. Hal ini berarti bahwa antara status dan masa kerjamerupakan dua faktor yang saling independent. (4) Tidak terdapat perbedaan antara hasil belajar peserta didik dilihat dari status guru yang tersertifikasi dan hasil belajar peserta didik yang diajar oleh guru yang belum tersertifikasi di kota Mataram (5) terdapat perbedaan hasil belajar peserta didik dilihat dari masa kerja guru. (6) Tidak ada interaksi faktor hasil belajar peserta didik dilihat dari status dan masa kerja guru di Kota Mataram (7) Diperoleh profil guru PAI MTs di kota Mataram yang tersertifikasi yang secara umummemiliki profil baik.Kata kunci: Kompetensi, Guru PAI MTs, Sertifikasi.